PERILAKU PEMBELIAN TIDAK TERENCANA PADA MASYARAKAT PENERIMA DANA CSR MIGAS DI BOJONEGORO - Eka Adiputra; Nurul Mazidah (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2015)
The survey conducted by AC Nielsen organization described that approximately 85% of purchasing in modern shopping center was done by unplanned or impulse buying. The consumer involvement and money available factors of the consumers were supposed to motivate more the impulse buying behaviors. Fashion (apparel) was one of the possible products causing the impulse buying and moreover it involved the involvement factors. According to that, the impulse buying behaviors became phenomenon that interesting to be researched. The aim of this research was to analyze the influence of the fashion involvement and money available toward the fashion-oriented impulse buying behaviors through consumers’ positive emotion. The research was conducted in the biggest shopping center in Surabaya with the samples of 210 samples of the visitors of the mall who had purchasing the fashion product. The data analyses were by using SEM and the 20th version of AMOS program. The result of the research pointed out that fashion involvement significantly be influenced toward the consumers’ positive emotion and the fashion-oriented impulse buying behaviors, the consumers’ positive emotion wasn’t influenced toward the fashion-oriented impulse buying behaviors. Money available was influenced significantly toward the consumers’ positive emotion and the fashion-oriented impulse buying behaviors.